1999
DOI: 10.1086/514774
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Aspergillus Osteomyelitis

Abstract: Aspergillus species are uncommon etiologic agents of vertebral osteomyelitis. We describe two patients with lumbar vertebral aspergillosis precipitated by the use of corticosteroids and review 39 cases in the literature. The mean age of the population was 40.04 years. There was male predominance (78% of cases), mainly lumbar involvement (53.7%), and monomicrobial nature of infection; 65.8% of the patients had predisposing factors, while 34.1% had none. Back pain (53.6% of cases) was the predominant symptom, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 36 publications
2
54
0
3
Order By: Relevance
“…Itraconazole is a newer drug which is given orally and is well tolerated. A few authors have reported good results with the use of itraconazole in spinal aspergillosis [5][6][7]21]. The patient presented here was also treated by oral itraconazole and responded well without any signs of toxicity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Itraconazole is a newer drug which is given orally and is well tolerated. A few authors have reported good results with the use of itraconazole in spinal aspergillosis [5][6][7]21]. The patient presented here was also treated by oral itraconazole and responded well without any signs of toxicity.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that, when the only symptom is back pain without significant instability or neural compression, medical treatment alone is sufficient. When spinal instability or symptoms of spinal cord or radicular compression are present, surgical decompression is indicated [21].…”
Section: Discussionmentioning
confidence: 99%
“…Eismont et al reported fungal organisms as the agent in 61 cases in the retrospective vertebral infection study they carried out (14). Vinas et al (15) in their systematic compilation stated that A.fumigatus was the agent in 71% of the 39 vertebral infections caused by Aspergillus types in the literature of 1966-1998. Vinas et al (15) detected underlying diseases including hematological malignancy, chronic granulamatosis, organ transplantation, corticosteroid use, surgical intervention history, tuberculosis in most of the patients in their study, while no immunosuppressants were reported in three patients as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Vinas et al (15) in their systematic compilation stated that A.fumigatus was the agent in 71% of the 39 vertebral infections caused by Aspergillus types in the literature of 1966-1998. Vinas et al (15) detected underlying diseases including hematological malignancy, chronic granulamatosis, organ transplantation, corticosteroid use, surgical intervention history, tuberculosis in most of the patients in their study, while no immunosuppressants were reported in three patients as in our case. Fibrous dysplasia and Aspergillus infections may interfere in the clinical diagnosis (16), however in our case there was a coexistence of Aspergillus infection and fibrous dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, Soler-Palacin et al (10) found that for patients aged 5 years and older, the median intravenous dose needed to achieve therapeutic levels was 15 mg kg Ϫ1 day Ϫ1 . Surgery is generally required when there is evidence of spinal cord (nerve root) compression or vertebral bony destruction (7,9).…”
mentioning
confidence: 99%